2012
DOI: 10.4049/jimmunol.1201000
|View full text |Cite
|
Sign up to set email alerts
|

A c-Myc and Surface CD19 Signaling Amplification Loop Promotes B Cell Lymphoma Development and Progression in Mice

Abstract: Malignant B cells responding to external stimuli are likely to gain a growth advantage in vivo. These cells may therefore maintain surface CD19 expression to amplify transmembrane signals and promote their expansion and survival. To determine whether CD19 expression influences this process, Eμ-Myc transgenic (c-MycTg) mice that develop aggressive and lethal B cell lymphomas were made CD19 deficient (c-MycTgCD19−/−). Compared with c-MycTg and c-MycTgCD19+/− littermates, the median life span of c-MycTgCD19−/− mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 51 publications
8
63
0
Order By: Relevance
“…It was, however, robustly induced upon SHP2 re-expression and could form a SHP2-dependent positive feedback loop that enhanced the transcription factor c-Myc and oncogenic RAS expression in some solid cancers. 30 Because the well-known synergy of cMyc and CD19 aberrant expression in Eμ-Myc transgenic mice was necessary for malignant B-cell transformation, 19 we examined using immunoblot analyses, whether SHP2 commonly contributed to the reciprocal regulation of CD19 and c-Myc by transcriptional activation and subcellular localization in GC lymphoma cells. As expected, lack of SHP2 resulted in suppression of both CD19 and c-Myc protein and their activation in GC lymphoma cells ( Figure 5A), whereas CD19 knockdown had no effect on the expression of SHP2 in GC lymphoma cells but significantly inhibited its Tyr542 phosphorylation in…”
Section: Myc/igh+mentioning
confidence: 99%
See 4 more Smart Citations
“…It was, however, robustly induced upon SHP2 re-expression and could form a SHP2-dependent positive feedback loop that enhanced the transcription factor c-Myc and oncogenic RAS expression in some solid cancers. 30 Because the well-known synergy of cMyc and CD19 aberrant expression in Eμ-Myc transgenic mice was necessary for malignant B-cell transformation, 19 we examined using immunoblot analyses, whether SHP2 commonly contributed to the reciprocal regulation of CD19 and c-Myc by transcriptional activation and subcellular localization in GC lymphoma cells. As expected, lack of SHP2 resulted in suppression of both CD19 and c-Myc protein and their activation in GC lymphoma cells ( Figure 5A), whereas CD19 knockdown had no effect on the expression of SHP2 in GC lymphoma cells but significantly inhibited its Tyr542 phosphorylation in…”
Section: Myc/igh+mentioning
confidence: 99%
“…19,20 Indeed, previous experimental data acquired through the use of Eμ-Myc transgenic mice demonstrated that the c-Myc/ERK/CD19 feedback signaling loop is important for the malignant transformation of B cells and in determining the severity of lymphomas. 19,20 Chromosomal overexpression of translocation-elicited c-Myc induces the transcription of cyclin and cyclin-dependent kinase (CDK) genes which also relies significantly on CD19/ERK cascade-mediated phosphorylation of c-Myc on Ser62. 19 Specifically, CD19-mediated MYC/IGH translocation-induced (MYC/IGH+) B-cell lymphomagenesis can be inhibited by deleting the scaffold protein kinase suppressor of RAS-1 (KSR1) or treatment with MEK/ERK inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations